Active faulting within a megacity: the geometry and slip rate of the Pardisan thrust in central Tehran, Iran - Talebian, M; Copley, A; Fattahi, M; Ghoraishi, M; Jackson, J; Nazari, H; Sloan, R; Walker, R (Oxford University Press, 2016)
Tehran, the capital city of Iran with a population of over 12 million, is one of the largest urban centres within the seismically active Alpine-Himalayan orogenic belt. Although several historic earthquakes have affected Tehran, their relation to individual faults is ambiguous for most. This ambiguity is partly due to a lack of knowledge about the locations, geometries, and seismic potential of structures that have been obscured by dramatic urban growth over the past three decades, and which have covered most of the young geomorphic markers and natural exposures. Here we use aerial photographs from 1956, combined with an ~1 m DEM derived from stereo Pleiades satellite imagery, to investigate the geomorphology of a growing anticline above a thrust fault – the Pardisan thrust - within central Tehran. The topography across the ridge is consistent with a steep ramp extending from close to the surface to a depth of ~2 km, where it presumably connects with a shallow-dipping detachment. No primary fault is visible at the surface, and it is possible that the faulting dissipates in the near surface as distributed shearing. We use optically-stimulated luminescence to date remnants of uplifted and warped alluvial deposits that are offset vertically across the Pardisan fault, providing minimum uplift and slip-rates of at least 1 mm/yr. Our study shows that the faults within the Tehran urban region have relatively rapid rates of slip, are important in the regional tectonics, and have a great impact on earthquake hazard assessment of the city and surrounding region.